Spectral and structural analysis on 2-(4-Allyl-5-Mercapto-4H-1,2,4-Triazol-3-yl)Acetic acid: Experimental and theoretical (HF and DFT) studies - Sen, Fatih; Dincer, Muharrem; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Elsevier, 2017)
We examined the structural and spectral features of the title compound through with experimental and electronic structure methods. The crystal and molecular structure of compound has been brought out using single crystal X-ray diffraction. The spectroscopic investigations of the compound were studied by FT-IR and NMR techniques. The FT-IR spectra were recorded in solid phase on a Mattson 1000 in the region 4000-400 cm(-1). H-1 and C-13 NMR spectra were recorded in deuterium oxide (D2O) chloroform solution on a Varian-Mercury-Plus 400 MHz spectrometer. To support experimental results, the structural and spectroscopic data of the molecular geometry which obtained from the X-ray molecular structure in the ground state were optimized by using Hartree-Fock (HF) and Density Functional Theory (DFT/B3LYP) methods with the 6-31-FG(d, p) basis set. The calculated structural parameters (bond lengths, bond angles, torsion angles), vibrational assignments and chemical shifts compared with their experimental data. The frontier molecular orbitals (FMOs), molecular electrostatic potential maps (MEP), Mulliken charge analysis and thermodynamic properties of the compound were obtained by theoretical geometries. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Triazole; Hartree-Fock (HF); Density functional theory; X-ray diffraction; HOMO and LUMO; Molecular electrostatic potential (MEP)